The Interconnected Factors of Migrant Land Issues for Sustainable Urban Development - Lestaluhu, Malfira; Lawelai, Herman (Jurnal Ranah Publik Indonesia Kontemporer (Rapik), 2024)
This research explores the interrelated factors in migrant land issues for sustainable urban development. Through a literature review using the PRISMA method, this study identified and analyzed 395 documents from the Scopus database for the period 2015-2024. Data visualization using InfraNodus revealed that rural-urban migration is a key driver of land use change, causing environmental and social challenges. This analysis highlights the importance of effective policies and adaptive management to address the negative impacts of migration on land use. Social integration and community support play a critical role in migrants' transition to urban areas and their contribution to sustainable urban development. The findings show that social, economic and environmental factors interact in complex ways, requiring a multidisciplinary approach to create inclusive and sustainable solutions. This research provides new insights for better urban planning and encourages further research to develop more sustainable urban development strategies. The overall findings are important in creating development strategies that balance urban growth with environmental sustainability and social well-being.